Pemberian minyak ikan lele (Clarias gariepinus) terhadap bobot badan dan perubahan histopatologi hati, ginjal, dan otak tikus galur Sprague dawley yang diberi pakan hiperkolesterolemia - Firmansyah, Hardi; Roosita, Katrin; Kusharto, Clara Meliyanti; Handharyani, Ekowati (Jurnal Gizi dan Pangan, 2017)
The objective of this study was to analyze changes in body weight and cell morphology in liver, kidney and brain tissue of Sprague dawley rats administered  hypercholesterolemia diets for four weeks. Four diet treatments were applied in this study: control, catfish oil, catfish oil with the addition of omega 3 and catfish oil with the addition of omega 3 and vitamin E. Four weeks after the intervention, the rats were sacrificed and the internal organs (liver, brain, and kidney) were taken for histological preparations by hematoxylin-eosin (HE) and immunohistochemistry test. The study showed that the catfish oil intervention tend to reduced weight gain of rats fed hypercholesterolemia diets. More lipid accumulation in liver of the control group was found than the intervention groups. However, there was no difference in the histopathology of the kidney and brain tissues between the control group and intervention groups. It is concluded that catfish oil study provides a positive effect in rat liver tissue, but no difference exists between the brain and kidney tissue. There is no defect found at hippocampus of rats by formed of amyloid plague.